KAJIAN POTENSI PENGEMBANGAN PERTANIAN PERKOTAAN DI KOTA SEMARANG - Wiwandari Handayani; Prihadi Nugroho; Dini Oktaviani Hapsari (Jurnal Riptek, 2018)
High urban population growth that are followed by prominent urbanization phenomena is a global issue. It raises challenges and problems in various aspects, such as a decrease in environmental quality due to reduced green space, and the need for adequate and quality food availability for the growing urban population. Accordingly, as has been implementing in most advanced urban areas worldwide, urban farming activities appears as a promising solution to supply a sustaingood quality agricultural products. The Semarang City Government has designated urban farming program to promote food resilience as one of the priority development issues stated in the RPJMD 2016-2021. Following the commitment, this study aims to elaborate potentials and co-benefits to further develop the urban farming activities within the city. Descriptive and spatial analyses supported by secondary and primary data were applied to assess the findings. There are two types of urban farming activities, those are (a) located in the outskirt of the city mostly using conventional approach, and (b) urban farming mostly in the city center applying hydroponic or other approaches those are suitable for limited space.The potentials are various including many kinds of vegetables, cassava, sugar cane, durian, and mushrooms. The co-benefits include different aspects (i.e. environmental, economic, social, health, education and tourism). Proper top-down and bottom-up policy instruments are very critical to ensure that the urban farming activity brings optimize benefit to the people as well as to the city.